Pengaruh Komunikasi Efektif terhadap Kecerdasan Emosional Anak Usia Dini - Nurul Aini MM Sodik; Esperansa Mile; Sri Mulyani; Fitri Adoe; Isnawaty Daintaw (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to analyze the influence of effective communication on the emotional intelligence of early childhood. Effective communication is the process of conveying clear, empathetic, and responsive messages between educators or parents and children, which plays a crucial role in shaping children's abilities to recognize, understand, and manage emotions. Emotional intelligence is an essential aspect of child development because it supports social adaptation, self-regulation, and positive interpersonal relationships. The research method used was a quantitative approach with a correlational design. The subjects were early childhood education institutions attending early childhood education institutions, with data collection techniques through observation, questionnaires, and documentation. Data were analyzed using statistical procedures to determine the relationship between the variables studied. The results showed a significant influence between effective communication and children's emotional intelligence. Children who receive good communication tend to have higher empathy skills, are able to control their emotions, and establish positive social relationships. In addition, effective communication helps children express their feelings appropriately and develop self-confidence. Thus, effective communication is an important factor in the development of emotional intelligence in early childhood. This research is expected to serve as a reference for educators and parents in improving the quality of interactions with children and supporting optimal child development.